Light hydrocarbons and diamondoids in deep oil from Tabei of Tarim Basin: Implications on petroleum alteration and mixing. (April 2022) - Chai, Zhi; Chen, Zhonghong; Patience, Richard; Wen, Zhigang; Tang, Youjun; Cheng, Bin; Li, Mingpeng; Luemba, Moïse; Wu, Zepeng
Abstract: The Tuofutai Bulge in central Tabei of northern Tarim Basin provides insights into the complex geochemical processes of deep oil accumulations. Fifteen crude oil samples collected from deep Ordovician reservoirs were tested and analyzed with light hydrocarbons (LHs) and diamondoids to evaluate the oil family, secondary alteration, and mixing processes. Results show that the oil samples share similar distribution characteristics of LHs and diamondoids and contain low concentrations of methyldiamantanes, suggesting that they belong to one group and have not been significantly altered by thermal cracking. Geochemistry of LHs and diamondoids indicate that the thermochemical sulfate reduction is limited and negligible, whereas some samples are severely altered by biodegradation. The phase fractionation is mainly related to the leakage of light hydrocarbon caused by geological activities such as tectonic uplift and fault activity, and some samples show weak evaporative fractionation. The biodegradation causes the increase in the values of methyladamantane to adamantane (MAs/A) and the concentrations of (1 + 2)-methyladamantane and (3 + 4)-methyldiamantane. The thermal maturity of oil calculated on the basis of LHs and diamondoids is generally higher than that calculated using saturated and aromatic fractions. The difference of various maturity parameters related to saturated hydrocarbon, aromatic hydrocarbon, LHs and diamondoids records multiple oil charging and mixing processes. Highlights: Light hydrocarbons and diamondoids of the deep oils was revealed. The deep oil suffered limited thermal cracking and weak evaporative fractionation. Significant biodegradation was revealed in some oil samples. Effect of biodegradation on diamondoid parameter was revealed. Different molecular maturity indicators reflect multiple charging and mixing.